FORMATION OF MEDIA COMPETENCE OF FUTURE DOCTORS IN THE PROCESS OF PRECLINICAL PROFESSIONAL TRAINING: PSYCHOLOGICAL AND PEDAGOGICAL CONDITIONS - Olena Murzina (Неперервна професійна освіта: теорія та практика)
The article theoretically substantiates the psychological and pedagogical conditions for the formation of media competence of future doctors in the process of preclinical professional training at the medical university. It is necessary to create appropriate psychological and pedagogical conditions to implement the process of forming media competence of future doctors in preclinical professional training at the medical university. Randomly selected conditions cannot significantly affect the effectiveness of the researched process, therefore a natural selection of a complex of psychological and pedagogical conditions is necessary, taking into account the methodological and theoretical basis of pedagogical research. By psychological and pedagogical conditions of the formation of media competence of future doctors in the process of preclinical professional training at the medical university we mean the complex of student’s personal characteristics and external circumstances of the educational process and the media environment that are aimed at the formation of media competence of future doctors in the process of preclinical professional training at the medical university. The psychological and pedagogical conditions for the formation of media competence of future doctors at the stage of preclinical professional training at the medical university are defined and substantiated: motivation of future doctors to master media competence, media knowledge and media literacy; creation of the media environment of the university; optimization of classroom and extracurricular educational interaction of participants in the educational process through the media environment creation including interactive media technologies; the use of media content both from the media environment of the university and the media space to create one’s own media product and apply it in education and future professional activities; constant use of media sources in the process of digital training. The specified psychological and pedagogical conditions for the formation of media competence of future doctors form the system that includes independent components that can be used in the process of preclinical professional training at the medical university and contribute to the effective formation of all components of media competence of future doctors.